Price transmission mecanism: an analysis of the brazilian melon exportations - Severino Félix de Souza; Jorge Luiz Mariano da Silva; João Ricardo Ferreira de Lima; João Paulo Martins Guedes (Economia Aplicada, 2017)
Environmental conditions consented to Brazil, since the major producer of tropical fruits. This article verifies the transmission melon prices, with Brazil, US market and the European Union from 2003 to 2013. Using time series data, the relationship between the prices was analyzed by estimates from a vector autoregression model (VAR) and the Granger causality test respectively. The results shows that the domestic prices are not influenced from others and influence the EU market, exerting more and more impact on the fluctuations of the international market affecting production expectations and marketing of producers.